2020
DOI: 10.1111/1750-3841.15136
|View full text |Cite
|
Sign up to set email alerts
|

A highly sensitive monoclonal antibody−based paper sensor for simultaneously detecting valnemulin and tiamulin in porcine liver

Abstract: Valnemulin (VAL) and tiamulin (TIA) are pleuromutilin antibiotics used primarily for treating bacterial infections in swine or other food animals. Furthermore, VAL and TIA are also employed as feed additives to promote animal growth. However, the illegal use of VAL and TIA could cause a series of hazards to consumers. Here, VAL was designed to be conjugated with bovine serum protein to prepare immunogen. A highly sensitive monoclonal antibody that recognized both VAL and TIA has been successfully produced. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…At the same time, icFLISA has no enzymatic reaction steps and saves washing times, which was more convenient than icELISA. Moreover, Lei et al (2018) and Na et al (2020) reported previously used monoclonal antibodies to establish icELISA for detection of TML, with IC 50 values of 0.36 ng/ml and 0.392 ng/ml, respectively. The results indicated that icFLISA based on QDs was more sensitive than traditional icELISA for TML detection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, icFLISA has no enzymatic reaction steps and saves washing times, which was more convenient than icELISA. Moreover, Lei et al (2018) and Na et al (2020) reported previously used monoclonal antibodies to establish icELISA for detection of TML, with IC 50 values of 0.36 ng/ml and 0.392 ng/ml, respectively. The results indicated that icFLISA based on QDs was more sensitive than traditional icELISA for TML detection.…”
Section: Resultsmentioning
confidence: 99%
“…The procedure of icELISA was similar to a previously described method (Chen et al, 2020; Lei et al, 2018; Na et al, 2020). The transparent polystyrene 96‐well microtiter plates were coated with 100 μl TML‐OVA, which diluted with CBS buffer and incubate at 37°C for 2 hr.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the activated mixture was added dropwise to a protein solution (6 mg of BSA was dissolved in 2 mL carbonate–bicarbonate buffer, pH 9.6) with stirring overnight at 4 °C. Lastly, the resulting conjugate hapten A–BSA was dialyzed with PBS for 2–3 days and then stored at −20 °C for future use. …”
Section: Methodsmentioning
confidence: 99%
“…The process of ic-ELISA was analogous to a previously reported method (Na et al, 2020). The QCT-OVA was diluted to optimal concentration by CBS buffer and coated on a 96-well plate with 100 μl/ well.…”
Section: Ic-elisa Proceduresmentioning
confidence: 99%